2020
DOI: 10.3390/catal10010139
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Tunable Optical Absorption Plasmonic Au and Ag Decorated TiO2 Structures as Efficient Visible Light Photocatalysts

Abstract: Exploring solar-excited heterogeneous photocatalysts by taking advantage of surface plasmon resonance (SPR) has drawn growing research attention. As it could help to pave the way for global sustainable development. The decoration of TiO2 particles with noble metals possessing SPR effects is regarded as one of the most effective solutions. The perfect match of the SPR absorption band with the spectrum of incident light is an essential factor for plasmonic enhancement. However, modifying with sole noble metal is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The H 2 O 2 production may be sustained by incorporating a smaller amount of Au and Ag since k d is suppressed by reducing the loading while k f is less affected by the loading reduction. Interestingly, Yang et al recently reported the synthesis of the colloidal Au-Ag/TiO 2 , which shows an excellent photocatalytic efficiency for the degradation of methylene blue [40]. The Au-Ag loading ranged from 0.4 to 1.0 mol % and the maximal photoactivity was achieved by using Au 0.21 Ag 0.79 with NP = 0.82 mol % TiO 2 catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The H 2 O 2 production may be sustained by incorporating a smaller amount of Au and Ag since k d is suppressed by reducing the loading while k f is less affected by the loading reduction. Interestingly, Yang et al recently reported the synthesis of the colloidal Au-Ag/TiO 2 , which shows an excellent photocatalytic efficiency for the degradation of methylene blue [40]. The Au-Ag loading ranged from 0.4 to 1.0 mol % and the maximal photoactivity was achieved by using Au 0.21 Ag 0.79 with NP = 0.82 mol % TiO 2 catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Besides being cheap and relatively abundant, they boast an intense SPR effect that can offer superior plasmonic enhancement to the TiO 2 photocatalyst. The combination has been subjected to a couple of dye degradation studies for this reason [ 27 , 28 , 29 ]. Meanwhile, one-dimensional (1D) nanofibers serve as an appealing architecture for this application, as they can be convenient for separation and recovery [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Ag is relatively low cost compared to Au and the SPR effect can be tune in the visible region by changing the shape and sizes [14]. Again, controlling the size of NPs decorated on the metal-oxide is still challenging since the controlled growth technique need state-of-the-art fabrication technique [19]. Moreover, most of the recently reported techniques are not catalytic-free and employed more than one synthesis technique to develop photoanode for DSSCs [15,20].…”
Section: Introductionmentioning
confidence: 99%